Perinatal hepatitis B virus transmission in Lao PDR: A prospective cohort study - Vatthanaphone Latthaphasavang (2019)
© 2019 Latthaphasavang et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background Mother-to-child transmission of hepatitis B virus (HBV) is the main cause of new infections worldwide. We aimed at assessing the percentage of infants successfully immunized in two major hospitals in Vientiane, Lao PDR where HB immune globulin (HBIg) is not available. Methods We studied a prospective cohort of chronically HBV infected pregnant women and their infants until 6 months post-partum from January 2015 to March 2017. All infants received HB vaccine at birth and 6, 10 and 14 weeks thereafter, and HBV status was assessed at 6 months of age. HBV surface gene sequencing was performed in infected mother-infant pairs. Results Of 153 mothers with HB surface antigen (HBsAg), 60 (39%) had detectable serum HBe antigen (HBeAg). HBeAg positive pregnant women were younger than those negative (median age 26 versus 28 years; p = 0.02) and had a significantly higher HBV viral load at delivery (median 8.0 versus 4.0 log 10 IU/mL, p <0.001). Among the 120 infants assessed at 6 months of age, 5 (4%) were positive for HBsAg and had detectable HBV viral load by polymerase chain reaction. All were born to mothers with HBeAg and viral load >8.5 log 10 IU/mL. However, only four (3.3%, 95% CI 0.5% to 7.0%) had a virus strain closely related to their mother’s strain. HBV surface gene mutations were detected in 4 of the 5 infected infants. Anti-HBs antibody levels were below 10 IU/L in 10 (9%) uninfected infants at 6 months of age. Conclusions Mother-to-child transmission occurred less frequently than expected without the use of HBIg. Adding HBIg and/or maternal antiviral prophylaxis may have prevented some of these infections. The observation of unsatisfactory levels of anti-HBs antibodies in 9% of the uninfected infants at 6 months highlights the need for improvement of the universal immunization procedures.